ANALISA KEBUTUHAN TENAGA PERAWAT DI RUANG RAWAT INAP PRIA DAN WANITA RUMAH SAKIT UMUM MEURAXA KOTA BANDA ACEH TAHUN 2008 - Oktaviza, Yenni (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2011)
Yenni Oktaviza1, Amal Chalik Sjaaf2Peminatan AKK, Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, Banda Aceh, 23245Kajian Adm. Rumah Sakit, Fakultas Kesehatan Msyarakat, Universitas Indonesia, Kampus Baru Depok, Indonesia. AbstractPublic Hospital of Meuraxa Banda Aceh is one of the types B hospital of Aceh Province (RSUM). The estimation of nurses need for this hospital in year 2008 was done by using Workload Indicator Staffing Needs (WISN). This research was conducted both in male and female in-patients wards of hospital in September 2008. This is a descriptive research by using both qualitative and quantitative approach. The population was the whole activities of nurses working in both in male and female in-patients of male and female of the hospital. Sample was the nurse activities in wards of in-patients of male and female of the hospital by observing using work sampling forms and time record forms of the nurse main activities done by time observer (data collector). Qualitative approach was done by using in-depth interview to get information from the Heads of both male and female in patients’ wards. Compared to the available nurses in male ward was 12/7 = 1.71 (171%) or over 71%. The surplus ratio did not mean that many nurses did not work but by using WISN need rate they can improve productivity and quality service as well.Keywords : nurses needed, WISN, ward, service quality